2001
DOI: 10.1002/jmri.1216
|View full text |Cite
|
Sign up to set email alerts
|

Gadobenate dimeglumine‐enhanced magnetic resonance imaging of intracranial metastases: Effect of dose on lesion detection and delineation

Abstract: Seventy-four patients with one to eight proven intraaxial metastatic lesions to the brain received a total gadobenate dimeglumine dose of 0.3 mmol/kg of body weight, administered as three sequential bolus injections of 0.1 mmol/ kg, at 10-minute intervals over a 20-minute period. Quantitative and qualitative assessments of efficacy were performed after each injection and a full evaluation of safety was conducted. Cumulative dosing produced significant (P < 0.01) dose-related increases in lesion-to-brain (L/B) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 30 publications
3
16
0
1
Order By: Relevance
“…Concerning quantitative enhancement, the increases in CNR with gadobenate dimeglumine compared with gadodiamide on T1SE images were generally between 20% and 35%, which correspond to the magnitude of increase typically observed with a double dose of gadolinium contrast agent compared with a single dose. 17,18 Our results are similar to those of a recent intraindividual crossover comparison of 0.1-mmol/kg BW gadobenate dimeglumine with an identical dose of gadopentetate dimeglumine 8 and may be attributed to the roughly twofold higher R1 relaxivity of gadobenate dimeglumine in blood. [3][4][5][6] This twofold higher R1 relaxivity, which is independent of the field strength of the MR magnet, 3 is due to weak and transient interactions of the Gd-BOPTA molecule with serum albumin, 5,6 which slow the tumbling rate of the Gd-BOPTA complex in blood.…”
Section: Discussionsupporting
confidence: 87%
“…Concerning quantitative enhancement, the increases in CNR with gadobenate dimeglumine compared with gadodiamide on T1SE images were generally between 20% and 35%, which correspond to the magnitude of increase typically observed with a double dose of gadolinium contrast agent compared with a single dose. 17,18 Our results are similar to those of a recent intraindividual crossover comparison of 0.1-mmol/kg BW gadobenate dimeglumine with an identical dose of gadopentetate dimeglumine 8 and may be attributed to the roughly twofold higher R1 relaxivity of gadobenate dimeglumine in blood. [3][4][5][6] This twofold higher R1 relaxivity, which is independent of the field strength of the MR magnet, 3 is due to weak and transient interactions of the Gd-BOPTA molecule with serum albumin, 5,6 which slow the tumbling rate of the Gd-BOPTA complex in blood.…”
Section: Discussionsupporting
confidence: 87%
“…As noted in comparisons with other GBCAs, 5-8 the increase in CNR with gadobenate dimeglumine compared with gadobutrol can be considered comparable with the magnitude typically observed with a double dose of GBCA compared with a single dose. 21,22 Although comparable enhancement to that achieved with gadobenate dimeglumine might have been obtained with a double dose of gadobutrol (ie, an identical volume), injections of high doses of GBCAs are not to be recommended, given the risk of NSF in certain patients with severe renal impairment. In this regard, although gadobutrol is a macrocyclic agent and thus widely considered one of the "safer" GBCAs, cases of NSF following its sole injection have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Early dosing studies demonstrated that, as expected, double doses of gadobenate dimeglumine (MultiHance®) are potentially beneficial with increased sensitivity in brain lesion detection, but, unlike other contrast agents, no further benefit is derived from triple doses [15,19]. However, the more significant evidence of improved diagnostic performance with the higher relaxivity agent derives from a series of intraindividual crossover studies directly comparing gadobenate dimeglumine (MultiHance®) with gadopentetate dimeglumine (Magnevist®, Bayer Schering Pharma AG, Berlin, Germany) [20][21][22][23][24][25], gadoterate meglumine (Dotarem®, Guerbet Aulnay s/ Bois, France) [20,22], gadodiamide (Omniscan™, GE Healthcare AS, Oslo, Norway) [20,26] and gadofosveset trisodium (Vasovist®) [6].…”
Section: Applications Of Contrast-enhanced Mri In Neuroimagingmentioning
confidence: 98%
“…In light of the excellent safety profile of CE-MRI with Gd contrast agents, the use of higher doses became routine clinical practice when determination of the disease extent was the main goal of the examination. However, higher doses of contrast agent increased the cost of MRI and were associated with potentially more false-positive results [14,15]. Additionally, of late, there has been increased concern for the development of nephrogenic systemic fibrosis (NSF) in at-risk patients when higher doses are used [16][17][18].…”
Section: Applications Of Contrast-enhanced Mri In Neuroimagingmentioning
confidence: 99%